Identification and Single‐Cell Analysis of Viable Circulating Tumor Cells by a Mitochondrion‐Specific AIE Bioprobe. Issue 4 (16th January 2020) - Situ, Bo; Ye, Xinyi; Zhao, Qianwen; Mai, Liyao; Huang, Yifang; Wang, Siqi; Chen, Jing; Li, Bo; He, Bairong; Zhang, Ye; Zou, Jianjun; Tang, Ben Zhong; et al.
Abstract: Liquid biopsies of cancer via single‐cell molecular profiling of circulating tumor cells (CTCs) are hampered by the lack of ideal CTC markers. In this study, it is reported that TPN, a bioprobe with aggregation‐induced emission (AIE) activity is capable of distinguishing various tumor cells from blood leukocytes based on the difference in cell mitochondria. TPN is a cell‐permeant live‐cell stain that has little effect on cell viability and integrity, enabling single‐cell DNA/RNA analysis with improved efficiency compared with traditional antibody‐based methods. Using TPN labeling, CTCs and CTC cluster are detected in the blood from patients with lung or liver cancer. The capability of TPN to identify rare tumor cells in the malignant pleural effusion samples is also demonstrated. Furthermore, RNA sequencing of single lung CTC identified by TPN is successfully performed. The findings presented here provide an antibody‐free, low‐cost, and nondisruptive approach for detection and genomic characterization of viable tumor cells based on a mitochondria‐targeting AIE luminogen. It might serve as a new tool for monitoring of genomics dynamic of tumor and unraveling the mechanisms of tumor metastasis. Abstract : A mitochondria‐targeting bioprobe with aggregation‐induced emission (AIE) activity for detecting rare tumor cells in the blood and pleural effusion from cancer patients is presented. The cell‐permeant, low toxic bioprobe enables genomic analysis of single tumor cells with improved performance, and can serve as a promising tool for liquid biopsy to obtain cancer genetics.